Sustainable approach for cassava processing in Africa - Sanni, Lateef O.; Abass, A.; Dixon, A.; Tarawali, G.; Westby, Andrew (International Institute of Tropical Agriculture, 2010)
Cassava plays important roles. It is a famine reserve crop, a staple food for the rural populace and a cash crop for urban consumption. It is a source of industrial raw materials and earns foreign exchange. Unfortunately, the past decades witnessed too much emphasis on the production components of the research industry in Africa. Yesterday, traditional processing offered a low value, poor quality product and used poor storage methods with a low investment drive to restricted consumers. Today, a shift toward higher value products and systems has been initiated through various sustainable research based approaches by the international research institutes. There are a few micro-, cottage, and small-medium enterprises for processing traditional cassava products along with a few large-scale factories for cassava starch in Africa, especially Nigeria, Ghana, Tanzania, and South Africa. The paper highlighted various constraints being faced today by cassava processors in Africa. Two major problems are still the peeling and drying processes. The future of cassava processing rests on effective implementation of those cassava initiatives and development of commercial “windows” for cassava processors through networking, partnership, advocacy, documentation, dissemination in different languages, mentorship, and enhanced marketing linkages of cassava produce with high levels of added-value products.